2020
DOI: 10.1128/mcb.00098-20
|View full text |Cite
|
Sign up to set email alerts
|

USP15 Deubiquitinates TUT1 Associated with RNA Metabolism and Maintains Cerebellar Homeostasis

Abstract: Precise regulation of RNA metabolism is crucial for dynamic gene expression and controlling cellular functions. In the nervous system, defects in RNA metabolism are implicated in disturbing brain homeostasis and development. Here we report that deubiquitinating enzyme, ubiquitin specific peptidase 15 (USP15), deubiquitinates terminal uridylyl transferase 1 (TUT1) and changes global RNA metabolism. We found that the expression of USP15 redistributes TUT1 from nucleolus to nucleoplasm, resulting in the stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…A defect in Usp15 increases the probability of splicing error and produces various abnormal variants. We also found that impaired USP15 induces the endoplasmic reticulum (ER) stress although the mechanism linking splicing error to ER stress has not been clarified 18 (Fig.1A). Because Usp15 gene is linked to ASD 2,19,20 , we looked for the ASD-associated abnormal variants, which have changed splicing upon Usp15 deficiency and are involved in the UPR pathway.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…A defect in Usp15 increases the probability of splicing error and produces various abnormal variants. We also found that impaired USP15 induces the endoplasmic reticulum (ER) stress although the mechanism linking splicing error to ER stress has not been clarified 18 (Fig.1A). Because Usp15 gene is linked to ASD 2,19,20 , we looked for the ASD-associated abnormal variants, which have changed splicing upon Usp15 deficiency and are involved in the UPR pathway.…”
Section: Resultsmentioning
confidence: 94%
“…Previously, we reported that the deubiquitinating enzyme, USP15, deubiquitinates U6 snRNA-specific terminal uridylyl transferase 1 (TUT1) and regulates the spliceosome cascade 18 . A defect in Usp15 increases the probability of splicing error and produces various abnormal variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…USP15 acts in certain diseases through the transcriptional regulation of target genes. USP15 deubiquitinates and redistributes terminal uridylyl transferase 1 (TUT1) from the nucleolus to the nucleoplasm, resulting in the stabilization of U6 snRNA, thereby regulating the neurodegenerative phenotype [ 105 ]. USP15 also deubiquitinates and opposes R-SMAD monoubiquitylation to prevent R-SMADs recognizing the promoters involved in the differentiation of mesenchymal stem cells from osteoblasts [ 106 ].…”
Section: Function Of Usp15 In Cancers and Other Diseasesmentioning
confidence: 99%
“…USP15 is a DUB that belongs to the USP family and is involved in numerous functions. USP15 deubiquitinates the Ub E3 ligase MDM2, eukaryotic initiation factor 4A-I (EIF4A1), terminal uridylyl transferase 1 (TUT1), and FK506-binding protein 5 (FKBP5) [ 109 , 110 , 111 , 112 , 113 ]. TRAF-interacting protein with a forkhead-associated domain B (TIFAB) has been implicated in various cellular signaling pathways associated with hematopoietic and immune cells [ 114 ].…”
Section: Deubiquitination In Amlmentioning
confidence: 99%